ҚАЗАҚСТАНДАҒЫ ТҰРҒЫН ҮЙ ҚҰРЫЛЫСЫНЫҢ НАРЫҚТЫҚ МЕХАНИЗМДЕРІН САРАПТАУ - Жұмабеков, Х Ы (Journal of Economic Research & Business Administration, 2015)
In given article the analysis of a market mechanism and law of functioning of the market of habitation Kazakhstan are considered.